2020
DOI: 10.20473/amnt.v4i4.2020.299-306
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Antioxidant Activity Level of Shredded Banana Flower-Chicken Meat

Abstract: Background: Data Riskesdas 2013 shows that the average amount portion of vegetable consumption in people aged 10 years or older is only 0.5 portions while the vegetable consumption category is said to be "sufficient" is at least 5 portions per day for 7 days a week. Banana blossom is a vegetable and commonly found in Bangka Belitung Islands Province. Banana blossom processing as a source of vegetables rich in antioxidant compounds and chicken meat as a source of animal protein, needs to be done by processing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Previous research related to the quality of fish floss with banana blossom as the main ingredient and the results can be concluded that the use of banana blossom in making shredded is included in the good category [16]. Shredded banana chicken meat has a good acceptability [17]. A similar study related to banana blossom fortification in the manufacture of fish floss from small tuna (Euthynnus affinis) was also conducted by Kartikaningsih et al [18].…”
Section: Organolepticmentioning
confidence: 92%
“…Previous research related to the quality of fish floss with banana blossom as the main ingredient and the results can be concluded that the use of banana blossom in making shredded is included in the good category [16]. Shredded banana chicken meat has a good acceptability [17]. A similar study related to banana blossom fortification in the manufacture of fish floss from small tuna (Euthynnus affinis) was also conducted by Kartikaningsih et al [18].…”
Section: Organolepticmentioning
confidence: 92%
“…According to the researchers, banana flower products formed at a 25% level displayed the highest preference in color, taste, aroma, texture, and overall acceptance. Additionally, it showed the highest antioxidant property (53.74% of DPPH radical scavenging activity) (Novidiyanto et al, 2020). However, its extract has also been used in burgers and sausages.…”
Section: Applications Of Banana and Its By‐products In Food Industrymentioning
confidence: 99%
“…It is interesting to note that in meat production, banana inflorescence has been combined with chicken flesh to create shredded banana inflorescence-chicken meat [ 66 ]. The researchers discovered that the products created with the assistance of inflorescences at a level of 25% had the highest preferences in terms of scent, taste, texture, color, and general acceptance.…”
Section: Banana Inflorescencementioning
confidence: 99%